Electron- and proton-impact excitation of hydrogenlike uranium in relativistic collisions - Gumberidze, Alexandre; Surzhykov, Andrey; Voitkiv, Alexander B.; Winters, Danyal Ferdinant Alexander; Winters, Natalya (Physical review letters, 2013)
The K shell excitation of H-like uranium (U91+) in relativistic collisions with different gaseous targets has been studied at the experimental storage ring at GSI Darmstadt. By performing measurements with different targets as well as with different collision energies, we were able to observe for the first time the effect of electron-impact excitation (EIE) process in the heaviest hydrogenlike ion. The large fine-structure splitting in H-like uranium allowed us to unambiguously resolve excitation into different L shell levels. State-of-the-art calculations performed within the relativistic framework which include excitation mechanisms due to both protons (nucleus) and electrons are in good agreement with the experimental findings. Moreover, our experimental data clearly demonstrate the importance of including the generalized Breit interaction in the treatment of the EIE process.